COLLABORATIVE GOVERNANCE DALAM PENANGGULANGAN KEMISKINAN DI KABUPATEN BANGKALAN PROVINSI JAWA TIMUR - Nur Handayani; Riza Risyanti; Suripto Suripto; Fernandes Simangungsong (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2023)
Abstract This study aims to describe collaborative governance in poverty reduction in Bangkalan Regency, the responsible parties and what poverty reduction strategies are used in Bangkalan Regency, East Java Province. The method used is descriptive qualitative with a theoretical approach from Ansell and Gash (2007) as the basis for the study in this research. Data were collected by interview, observation and documentation techniques and then analyzed by data reduction, data presentation, conclusion and verification. The results of the study indicate that coolaborative governance in poverty reduction in Bangkalan Regency has not run effectively in terms of initial conditions, institutional design, facilitative leadership, and collaborative processes due to the absence of uniform standards and perceptions of the poor. The regent as the person in charge and the stakeholders who are members of the TKPKD in poverty alleviation refers to the policy framework established by the government in poverty alleviation. It is deemed necessary to have a common perception of the standards of the poor at the central and regional levels and to synchronize data on the poor periodically so that their validity is guaranteed. Keywords: coolaborative governance, poverty, Bangkalan